The Impact of Green Marketing Techniques on Consumer Purchasing Decisions in Organic Product Companies in North Sumatra through Product Quality Perception as an Intervening Variable - Welly Arifin, Indra; Handayani Harahap, Hastuti; Rudy Sentosa Rajagukguk, Frederick (Lafadz Jaya Publisher, 2025)
This study aims to analyze the effect of green marketing techniques on consumer purchase decisions through perception of product quality as an intervening variable in organic product companies in North Sumatra. The method used in this study is a quantitative method using Structural Equation Modeling (SEM) through SmartPLS software. The test results show that green marketing techniques have a significant effect on the perception of product quality, which in turn affects consumer purchasing decisions. In addition, the perception of product quality is proven to be a variable that mediates the relationship between green marketing and purchasing decisions. These findings indicate that companies that implement green marketing techniques can improve the perception of product quality, which ultimately encourages consumers to buy the product. This study provides important insights for organic product companies to optimize green marketing strategies to improve consumer purchasing decisions.